Analisis Indeks Kesesuaian dan Daya Dukung Ekowisata Pantai di Pantai Panrita Lopi Teluk Pangempang Kecamatan Muara Badak, Kabupaten Kutai Kartanegara, Kalimantan Timur - Nurfadilah Dilah Nurfadilah; Muhammad Yasser; Irene Gloria Hutapea; Muhammad Agus Darmawan (Universitas Teuku Umar, 2022)
Panrita Lopi Beach is one of the tourist sites that has the potential as beach tourism, but this location has not been tested to determine the level of ecotourism suitability analysis and development of tourism management. This research was conducted in January 2022 using the IKW and SWOT methods. The results obtained based on the Coastal Ecotourism Conformity Index obtained the parameter values for depth, beach type, beach width, slope and current speed with a score of 4 (the highest) so that the IKW results with a value of 86% with the appropriate category, so that the location is good to be used as an ecotourism location. beach. Meanwhile, based on the SWOT analysis for the development of coastal tourism, it can be done with a focus on the development of facilities management strategies and cooperation with the government and private parties.